Characterization of essential oils and biological activities of Etlingera spp. from different agroecology in Southeast Sulawesi, Indonesia - SELFYANA AUSTIN TEE; SYAMSU ALAM; YURIKA SASTYARINA; AGUNG WIBAWA MAHATVA YODHA; REYMON REYMON; MUH. AZDAR SETIAWAN; MUSDALIPAH MUSDALIPAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Tee SA, Alam S, Sastyarina Y, Yodha AWM, Reymon, Setiawan MA, Musdalipah. 2025. Characterization of essential oils and biological activities of Etlingera spp. from different agroecology in Southeast Sulawesi, Indonesia. Biodiversitas 26: 1653-1665. Genus Etlingera, a part of Zingiberaceae, shows potential due to secondary metabolites influenced by agroecological factors, enhancing its therapeutic uses. The study aimed to characterize essential oils and biological activities of Etlingera elatior, Etlingera rubroloba, and Etlingera calophrys rhizomes collected from South Konawe, Wakatobi, and Muna District. Gas Chromatography-Mass Spectrometry (GC-MS) profiled the essential oils, while phenolic (TPC) and flavonoid (TFC) concentrations were determined using Folin-Ciocalteu and aluminum chloride methods. Antioxidant activity was assessed using DPPH and ABTS assays, and toxicity testing was performed on shrimp larvae. The research found that multiple species grow in areas with annual rainfall ranging from 1,800-2,100 mm/year, temperatures of 23-30°C, humidity levels of 78-84%, topography of 9-72 masl, and pH of 4.9-6.5. The essential oil content includes fatty acids (20.1-42.48%), phenolic (6.28-29.52%), and terpenoid (1.24-2.39). The IC50 of antioxidant activity (ABTS) for E. elatior, E. rubroloba, and E. calophrys were 1.3 mg/mL, 1.5 mg/mL, and 1.1 mg/mL, compared to vitamin C at 2.23 mg/mL. The DPPH assay IC50 values were 2.09 mg/mL, 2.17 mg/mL, and 2.42 mg/mL, compared to vitamin C at 2.78 mg/mL, respectively. TPC values were 113.63 mgGAE/g, 26.56 mgGAE/g and 143.00 mgGAE/g, respectively. TFC values were 62.03 mgQE/g, 21.07 mgQE/g, and 34.51 mgQE/g, respectively. Toxic LC50 values for extracts were 6.98 mg/L, 18.72 mg/L, and 120.86 mg/L compared to the positive control at 3.24 mg/L. The Structural Equation Models (SEM) approach demonstrates the direct and indirect influence of climatic and soil factors on secondary metabolites and biological activity of the genus Etlingera. In conclusion, the genus Etlingera is a promising source of antioxidants and anticancer agents. It is recommended for cultivation in suitable locations in Southeast Sulawesi, instilling hope and optimism about the future of this research.